Sputnik and the Republic: Education and War in Plato and the United States. - Virdis, Robert (My University, 2000)
This thesis is a discussion of the issue of public support for education. Educators in contemporary North America are finding it increasingly difficult to attract public dollars to educational institutions. Life in modern society is highly complex and specialized. It is unlikely that all people can become proficient in all activities that are vital for sustaining our way of living. Consequently, it is unlikely that the general public can come to anything but a vague understanding about most of the practices in our educational institutions. A central question emerges: How can educators persuade the general public to provide resources for specialized services that the average person can only have a vague understanding of? Those concerned about the issue of public support for education can look to recent American history for an example of a time when the public enthusiastically supported educational institutions. After the launch of the Soviet satellite "Sputnik" on October 4, 1957, there was an outpouring of public support for education in the United States. When considering this event, the historical observer is confronted by a perplexing consideration: What is the relationship between Sputnik and support for education in the United States? The thesis begins with an examination of Plato's Republic in order to outline a special connection that Socrates makes between education and war. According to Socrates' argument, if the average citizen is persuaded that education is readily and directly applicable to the attempt to provide the conditions under which the city will be better fortified against enemies, then the city will support educational activities of which they have no precise understanding, The discussion in Plato's Republic of the connection between education and war is a theoretical backdrop against which the flourishing of educational institutions during the post-Sputnik era can be examined, Plato's Republic helps modem readers to recognize the significance of evidence demonstrating that American pride and fear over the increasing technological and scientific capacity of their ideological rivals resulted in unprecedented public support for educational institutions.
Keywords: Political Science; Political Science